The ancient catechumenate: A brief liturgical-historical sketch. - Wepener, Cas (Stellenbosch Theological Journal, 2023)
In this article the development of the ancient liturgical-didactic practice of the catechumenate is explored by making use of both primary and secondary liturgical-historical sources. The aim is to sketch a liturgical-historical overview regarding the rise, the flourishing, and the demise of the catechumenate; describing what the catechumenate involved, why it existed as well as reasons for changes to this Christian practice from the late fourth century AD onwards. The description commences in the first decades of the history the Christian Church and ends in the later medieval period and before the onset of the Reformation when what was known as the catechumenate ceased to exist and disappeared as Christian liturgical practice of initiation. In conclusion, the potential value of this ancient practice for current day liturgical praxis is summarised.